Capitalism, imperialism, and modes of exchange: a reply to Karatani. Issue 2 (3rd April 2018) - Wainwright,
Abstract : ABSTRACT This paper is a response to Kojin Karatani's article, "Neoliberalism as a historical stage". Wainwright argues that Karatani elucidates the relationship between capitalism, imperialism, and empire by extending the mode of exchange theory Karatani has been developing over his career. Wainwright explains Karatani's radical reinterpretation of Marxist theory of empire and imperialism, distinguished based on their predominant mode of exchange: empire results from plunder/protection, imperialism from market/capital. In other words, empire and imperialism are neither epiphenomenal nor strategies waiting to be mobilized by political leaders. Rather, both are historical derivations of prevailing modes of exchange. Wainwright contends that these argument, though novel, do not reflect a radical break from Marx. Rather they reflect a return to Marx's original intuition that capitalism must be grasped through an analysis of production and exchange, extending Marx's analysis from Capital so as to explain other social relations. The global economic crisis (which neoliberalism has no means to resolve) and the persistent decline of US hegemony (with no clear alternative), coupled with the intensification of racialized, nationalist and religious forms of political difference, suggest that our world is entering a period of prolonged crisis, marked by imperialism and war. This is a reply to:Karatani, K. 2018. "Neoliberalism as a historical stage." Global Discourse. https://doi.org/10.1080/23269995.2018.1464614